Novel cobalt-free cathode material (Nd0.9La0.1)2(Ni0.74Cu0.21Al0.05)O4+δ for intermediate-temperature solid oxide fuel cells. Issue 1 (January 2015) - Zhou, Qingjun; Gao, Yuan; Wang, Fang; An, Dongmin; Li, Yan; Zou, Yunling; Li, Zepeng; Wang, Weibo
Abstract: The Ruddlesden–Popper phase, (Nd0.9 La0.1 )2 (Ni0.74 Cu0.21 Al0.05 )O4+ δ (NLNCA), has been investigated as an alternative cathode material for intermediate-temperature solid oxide fuel cells (IT-SOFCs). Its electrical conductivity is 51–60 S cm −1 over the temperature range of 650–800 °C. The average thermal-expansion coefficient (TEC) value of NLNCA is 13.2×10 −6 K −1 . The area specific resistance (ASR) of the NLNCA cathode measured on a Sm0.2 Ce0.8 O1.9 (SDC) electrolyte reaches a relatively low value of 0.048 Ω cm 2 at 800 °C. A maximum power density of 521 mW cm −2 is obtained at 800 °C for single-cell with thickness of 300 µm SDC electrolyte.